GENETIC DIVERSITY AND CHARACTER ASSOCIATION STUDIES FOR SOME ECONOMIC TRAITS IN RICE (ORYZA SATIVA L.) - VIJAY KUMAR, (The Bioscan, 2015)
An investigation was carried out to assess the nature and magnitude of genetic diversity was in 57 genotypes of rice using Mahalanobis D2 statistics. They were evaluated for thirteen yield and yield attributing characters and based on D2 analysis, 57 genotypes were grouped into 13 clusters. Clusters II and IV was the largest cluster containing 14 genotypes each followed by cluster III with 11 genotypes. The pattern of distribution of genotypes within different clusters was random and independent of geographical origin or region of adaptation. The characters like days to maturity (34.21%), days to flowering (27.44), grain length (19.55%) and grain width (12.16%) contributing maximum towards diversity. Hence these characters can be given consideration for selection of genotypes for future breeding programmes. The effective tillers (0.474), spikelet fertility (0.323), biological yield (0.723) and harvest index (0.744) in land races, plant height (0.542), panicle length (0.356), effective tillers (0.436), spikelet fertility (0.317), biological yield (0.766) and harvest index (0.744) in new plant types and panicle length (0.386), spikelets and grains per panicle (0.459, 0.498), biological yield (0.627) and harvest index (0.627)in japonicas were positively associated with grain yield indicating that these are the important characters and can be strategically used to improve the yield of rice.